(untitled) (Research, Society and Development, 2021)
Monitoring is one of the most important teaching, research and extension activities of higher education institutions, and there is also remote monitoring, which has the same objective and guidelines as in-person monitoring. In this sense, the article aims to describe the experience lived by students from the undergraduate nursing course at the CESMAC School of Sertão. This is a descriptive study, of the experience report type, whose narrative is based on a systematic observation of reality. An experience report was prepared in order to demonstrate innovative tools for teaching-learning, describing the Communication and Information Technologies used. In this perspective, facing the COVID-19 scenario new measures had to be adopted, and, thus, the college adopted the remote monitoring project that was distributed in disciplines of certain periods, enabling experiences, promoting the integration among students, supporting the development of the discipline and clarifying doubts. Thus, the remote monitoring program was taught by the college’s students under the guidance of their respective subject teachers. From this study, one can see the importance of remote monitoring for the students, in a way that this teaching-learning modality contributed to the formation of students, benefiting both the monitor and the one who is a listener/learning partner, sharing knowledge, adding a new way of seeing subjects and practices, and, therefore, being fundamental in future moments, in which the student will become a better professional.